An ABC of drumming: children's narratives about beat, rhythm and groove in a primary classroom. Issue 2 (16th April 2014) - Mackinlay, Elizabeth
Abstract : In this paper, I use a bricolage of arts-based research and writing practices to explore narratives by Grade 4 children about their experiences in a drumming circle called 'Bam Bam' as represented in a text they created with me called An ABC of drumming. The term 'narrative' is used here in a contemporary sense to simultaneously invoke a socially and musically situated and constructed story (Chase, 2005 p. 657); as an 'account to self and others' (Barrett & Stauffer, 2009, p. 7) about drumming in a particular place, with a particular group of children during a particular set of events; and, to explore narratives of drumming as the 'shared relational work' of myself as a drummer, teacher, researcher and 'story-teller/story-liver' (Connelly & Clandinin, 1990, p. 12) alongside the children. In synchronicity with the ABC of drumming produced by the children, the paper itself is framed and written creatively around letters of the alphabet and variously includes poetry and data or research poetry; ethnographic 'thick descriptions' (Geertz, 1973) of our drumming circle; and, visual and textual expressions by the children. By doing so, my aim is to move collectively from 'narrative as a "story-presented" to narrative as a "form of meaning-making", indeed, a form of "mind-making"' (Barrett & Stauffer, 2009, p. 10) about the children's experience of drumming and the drumming circle itself. The central question underpinning this paper then is, what makes children's experience in a drumming circle meaningful, and how do they make sense of such meaning?